Azathioprine induced anagen effluvium: a rare case report - Sharma, Saurabh; Budhiraja, Ravika K.; Bassi, Roopam (International Journal of Research in Dermatology, 2017)
Anagen effluvium occurs due to an agent or event that drastically reduces the metabolic activity of the matrix cells of the hair follicle. At any given time more than 80% of scalp hair is in the anagen phase of the hair cycle. Hence the resulting hair loss is abrupt and extensive. In majority of the cases, it occurs in association with cancer chemotherapy and radiation, other causes being rare. Here we report a case of a middle aged female suffering from Atopic dermatitis that was put on treatment with Azathioprine for the same. Treatment with Azathioprine was followed by a diffuse and extensive hair loss from the scalp associated with painful oral ulcers and marked leucocytopenia within a month of administration. The hair grew back within four months of stopping Azathioprine. This case report is an attempt to highlight a rare but extremely distressing side effect of Azathioprine which is a commonly used drug in dermatology.